High plasma nesfatin-1 level in Chinese adolescents with depression - Jin Sun; Nannan Gao; Qiong Wu; Yan Li; Li Zhang; Zhongliang Jiang; Zhiyi Wang; Jintong Liu (Scientific Reports, 2023)
Abstract Depression is a common psychiatric disorder with high prevalence and mortality rates as well as high risk of serious harm in adolescents that have significant negative impact on families and society. The feeding inhibitor Nesfatin-1 contributes to the regulation of stress and emotion. The purpose of this project was to compare the differences in the levels of Nesfatin-1 between adolescents with depression and healthy adolescents, and verify the association between the levels of Nesfatin-1 and severity of depression in adolescents. Adolescents with depression (n = 61) and healthy adolescents (n = 30) were evaluated. The Hamilton Depression Rating Scale (HAMD-17) was used to classify the adolescents with depression. Thirty-one and thirty-two was assigned to the mild-to-moderate (HAMD-17 ≤ 24) depression group and severe group (HAMD-17 > 24). Plasma Levels of Nesfatin-1 were measured by human ELISA Kit and differences among groups evaluated. Data were analyzed using the statistical software SPSS 23. HAMD-17 score was significantly higher in adolescents with depression than that in the healthy adolescents (P < 0.001). Median plasma Nesfatin-1 levels in adolescents with depression and healthy adolescents differed significantly at 37.3 pg/ml (22.1 pg/ml, 63.6 pg/ml) and 18.1 pg/ml (10.0 pg/ml, 25.7 pg/ml) (p < 0.001). A multivariate logistic regression analysis showed high plasma Nesfatin-1 concentrations were associated with increased risk of depression (OR = 0.914, 95% CI 0.87–0.96, P < 0.001). The receiver operating characteristic curve showed that the area under curve were 0.808 (95% CI 0.722–0.894, P < 0.001). Plasma Nesfatin-1 cut-off point of 32.45 pg/mL showed 59% sensitivity and 100% specificity. Median plasma Nesfatin-1 levels in the severe depression group (n = 30), mild-to-moderate depression group (n = 31), and control group (n = 30) were 53.4 pg/ml (28.2 pg/ml, 149.1 pg/ml), 29.9 pg/ml (14.5 pg/ml, 48.5 pg/ml) and 18.1 pg/ml (10.0 pg/ml, 25.7 pg/ml), and differed significantly among the three groups (P < 0.001). Median plasma level of Nesfatin-1 in males (n = 20) was 38.6 pg/ml (23.5 pg/ml, 70.1 pg/ml), while that in females (n = 41) was 37.3 pg/ml (22.0 pg/ml, 63.6 pg/ml), which was not a significant difference (P > 0.05). Plasma levels of Nesfatin-1 increased with severity of depression in adolescents and may be useful as a biomarker of depression severity. Further studies are needed in future projects.